Perbandingan Kinerja 4 Mesin ATF Charger untuk Proses Flashing pada Transmisi Toyota Yaris Matic - Wanda Wanda; Koswara Koswara; A Djoko Wiyono (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT This research is an experiment testing several Automatic Transmission Fluid (ATF) charger machines in the Flushing process during oil changes by comparing several ATF machines with the Toyota Yaris automatic transmission hydraulic pump. By knowing the performance of each of these tools, we can recommend a better and more efficient use for automatic car maintenance. The purpose of this study was to compare the ATF Charger Lounch Cat-501s, ATF Charger brand X1, ATF Charger brand X2 with a Toyota Yaris automatic transmission hydraulic pump. By knowing the performance of each of these tools, we can recommend a better and more efficient use for automatic car maintenance. besides that it also aims to find out the maintenance of the automatic transmission on the Toyota Yaris automatic transmission hydraulic pump. The method in this study uses experimental methods by conducting literature studies, sample preparation, group division, treatment implementation, measurement and observation and measurement of the speed of oil entering the transmission during flashing, data analysis, data interpretation, and report generation. The data collected includes efficiency, output power, generated pressure, costs incurred including maintenance costs. In addition, testing was also carried out to evaluate the performance of the Toyota Yaris automatic transmission hydraulic pump when using each type of ATF Charger machine during Flushing. The results showed that the ATF Brand X1 engine had the fastest performance in the process of changing the engine oil for the transmission of the Toyota Yaris automatic car, which was able to drain 1000 ml in 17.65 seconds, the speed was around 850 rpm (revolutions per minute), with an electric voltage of 12 Volts, as well as the cost of procuring the lowest equipment, which is IDR 1,807,530 Keywords: ATF Charger, Toyota Yaris, Matic